2017
DOI: 10.1021/acs.langmuir.6b04235
|View full text |Cite
|
Sign up to set email alerts
|

How High Concentrations of Proteins Stabilize the Amorphous State of Calcium Orthophosphate: A Solid-State Nuclear Magnetic Resonance (NMR) Study of the Casein Case

Abstract: ABSTRACT:Understanding how proteins stabilize Amorphous Calcium ortho-Phosphate (ACP) phases is of great importance in biology and for pharmaceutical or food applications. Until now, most of the former investigations about ACP-protein stability and equilibrium were performed in conditions where ACP colloidal nanoclusters are surrounded by low to moderate concentrations of peptides or proteins (15-30 g.L -1 ). As a result, the question of ACP-protein interactions in highly concentrated protein systems has clear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(48 citation statements)
references
References 26 publications
2
46
0
Order By: Relevance
“…Solid-state NMR was also used to detect the presence of hydrogen bonding from non-phosphorylated parts of the caseins to amorphous calcium phosphate nanoclusters [94]. The protons of the side chains of Arg, Lys, Glu or Asp can be close in space with P atoms, with a distance of 3.4-4.4 Å, and hence the terminal groups of the side chains including R-COOH and R-NH 2 have direct interactions with the inorganic phosphate of CCP [94].…”
Section: Nmr Studies On Casein Micellesmentioning
confidence: 99%
See 1 more Smart Citation
“…Solid-state NMR was also used to detect the presence of hydrogen bonding from non-phosphorylated parts of the caseins to amorphous calcium phosphate nanoclusters [94]. The protons of the side chains of Arg, Lys, Glu or Asp can be close in space with P atoms, with a distance of 3.4-4.4 Å, and hence the terminal groups of the side chains including R-COOH and R-NH 2 have direct interactions with the inorganic phosphate of CCP [94].…”
Section: Nmr Studies On Casein Micellesmentioning
confidence: 99%
“…Solid-state NMR was also used to detect the presence of hydrogen bonding from non-phosphorylated parts of the caseins to amorphous calcium phosphate nanoclusters [ 94 ]. The protons of the side chains of Arg, Lys, Glu or Asp can be close in space with P atoms, with a distance of 3.4–4.4 Å, and hence the terminal groups of the side chains including R-COOH and R-NH 2 have direct interactions with the inorganic phosphate of CCP [ 94 ]. Similarly, Cross et al [ 29 ], observing the β-casein peptide (1–25) interactions with amorphous calcium phosphate using NMR and molecular modeling, suggested that the entire length of the peptide is involved in interactions with calcium phosphate clusters.…”
Section: Nmr Studies On Casein Micellesmentioning
confidence: 99%
“…Many biofluids, including milk, contain phosphate and calcium in concentrations exceeding the limits of solubility that are stabilised by proteins [21]. Caseins fulfill this role through their natural ability to self-assemble into micelles in presence of calcium phosphate [61].…”
Section: Casein Delivery Particlesmentioning
confidence: 99%
“…Most of them form thermodynamically stable complexes with amorphous calcium phosphate, which accounts for 6 % of the micelle [2, 5]. Amorphous calcium phosphate forms spherical nanoclusters with diameter of 3.5–5.0 nm, spaced ~18 nm apart [21]. Phosphate is bound to the protein by phosphoseryl residues [22].…”
Section: Introductionmentioning
confidence: 99%
“…Such NMR studies also encompass the binding of small molecules, such as Pser, citrate, and amino acids, 15,16,28,29,31,40,41 as well as ACP interacting with Pser, 14 or Pser-bearing casein. 11,12 Given current limitations of a detailed experimental probing of the surface binding at atomic resolution, computer modeling by atomistic molecular dynamics (MD) simulations offers a rich source of structural information of the organic/inorganic interface, 27,29,41−54 enabling the extraction of the precise binding sites (atoms of a given functional group), as well as the detailed surface-immobilized molecular conformation hereafter referred to as the binding mode of the molecule. Such simulations typically target a three-component system that involves one or several biomolecules in an aqueous solution in contact with a slab of HA.…”
Section: Introductionmentioning
confidence: 99%